Pengaruh Word of Mouth dan Periklanan terhadap Keputusan Menjadi Nasabah di Bank Syariah Mandiri KCP Ulak Karang - Yasri, Yasri; Engriani, Yunita; Fitri, Melyawati (Jurnal Kajian Manajemen Bisnis, 2017)
This research aims to analyze the effect of word of mouth and advertising towards the customers decision to be customers of the Bank Syariah Mandiri KCP Ulak Karang. The population in this study are all potential customers Bank Syariah Mandir KCP Ulak Karang. Total sample is 150 respondents. It is taken by using accidental sampling. Primary data was obtained by using a questionnaire, while the secondary data is derived from documentation. Data analysis techniques used descriptive analysis and multiple regression analysis. The hypothesis was analyzed with the t test on alpha 0.05. Testing analysis usedSPSS version 23.00. Findings from this study are: (1) there is significant effects between word of mouth toward the customers decision to be customers of the Bank Syariah Mandiri KCP Ulak Karang with the percentage of the influence is 0.115 (2) there is significant influence between the advertising toward the customers decision to be customers of the Bank Syariah Mandiri KCP Ulak Karang with the percentage of the influence is 0.173.Â